Pipe Welding Jig for Greater Ease and Precision - Favid, Felix Alejandro; Alvin, Brandon; Fikri, Mohd Nabil; Budiman, Azme; Sariman, Mohd Firdaus; Idek, Sirhajwan (Future Science / FSH-PH Publications, 2025)
Pipe welding requires precision, stability, and safety to ensure results of acceptable quality. This study introduces a pipe welding jig designed to help welders maintain accurate 6G and 5G positions while reducing defects like misalignment and pipe distortion. The jig was designed to improve welding efficiency, safety, and precision, which makes the process easier and more consistent. A panel evaluation was conducted by five experts to assess four key aspects: design, ease of use, durability, and safety with an evaluation form with Likert-scale rating. The results were analyzed with Cronbach’s Alpha which revealed a score of 0.720 that showed the items were reliable. Experts rated the jig highly particularly on its stability, usability, and effectiveness in improving welding accuracy. This tool can benefit vocational training and industrial applications by minimizing errors and increasing productivity while helping to ensure welders’ wellbeing. Future improvements may include adjustable designs for various pipe sizes and automated features for enhanced efficiency.